Inside talent management: the strategic role of knowledge sharing and ICT capabilities in MNEs' performance. (27th February 2023) - Cillo, Valentina; Mazzucchelli, Alice; Pisano, Paola; Graziano, Domenico
Technological innovation is causing considerable changes on human resources management. In this scenario, one of the main issues Multinational Enterprises (MNEs) face concerns the ability to balance talent management. To this aim, the role of knowledge sharing and ICT capabilities is stressed in a number of researches. Starting from this scenario, this study attempts to analyse how the willingness to share knowledge, talent management effectiveness and ICT capabilities are related to the performances of MNEs. Data were collected using a web-based questionnaire divided into three sections and 25 items, using a five-point Likert. The target population of the study is formed by high tech MNEs from Italy. In order to better analyse knowledge sharing capabilities of talents, the context to carry out this research included a number of organisations operating in a knowledge intensive industry within the same context.